Batas Tanggung Jawab dalam Akad ‘Ariyah: Studi Komparatif Ulama’ Empat Mazhab - Hidayat Nur Wahid; Aditya Fa’ikhurozi; Aksamawanti (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2024)
society. Despite its social nature, the practice of the 'ariyah contract often raises legal issues, particularly regarding the limits of the borrower's liability in the event of damage or loss of goods. The differences in the views of scholars from four schools of thought regarding the status of this responsibility indicate a conceptual gap that requires a more systematic comparative study. This study aims to analyze the concept of the borrower's liability in the 'ariyah contract based on the perspectives of scholars from four schools of thought. This study aims to analyze the concept of the borrower's liability in the 'ariyah contract, identify differences and similarities in the views of scholars from four schools of thought, and also explain the pattern of the relationship between the principles of trust and liability in determining the limits of this responsibility. This study uses a qualitative method with a literature study approach, by examining classical fiqh literature and relevant Islamic legal sources. The results of the study indicate that in principle the borrower is positioned as a trustee, but this status can change to a liability if there is negligence, violation of permission limits, or misuse of goods. The difference between the two schools of thought lies in the definition of trust and liability. The Hanafi and Maliki schools tend to be more lenient, while the Shafi'i and Hanbali schools emphasize responsibility. This research contributes to clarifying the construction of responsibility in the 'ariyah contract as a basis for strengthening equitable muamalah practices.